(untitled) (Jurnal Adabiya, 2021)
Abstract The Abbasid dynasty had succeeded in placing the Islamic world at the pinnacle of world civilization. The achievements at that time were inseparable from the role of dakwah activities which were very comprehensive so that they were able to target all lines of community life. The synergy between the rulers and the people during the Abbasid government was proven to be able to give birth to many disciplines, not only religious knowledge, which in fact originated from the Al-Qur’an and hadith, but also gave birth to many general sciences such as medicine, philosophy, chemistry, economic and other science. The Khalifah as the holder of power supports a lot of preaching and scientific activities, this is evidenced by the construction of many supporting facilities and infrastructure such as mosques, madrasas, libraries and hospitals. In addition, the openness of Abbasid civilization also brought in people from various parts of the world, not only from Arab circles, people from Persians, Chinese, European, Indian and African who took part in filling in the diversity of scientific developments there. Then the economic condition of the community also has a very good record, such as in the field of Abbasid trade in its time as the center of world trade, as well as the agricultural sector, the Abbasid community is known to be prosperous, and has a very good life order. Therefore, the Abbasid dynasty could easily be applied in life in the current era, by building cooperation between the rulers and the community in developing da’wah because with the existence of a strong dakwah it was not lame in accordance with its essence and also followed the mission of da’wah so that it could be perfect, there needs to be good cooperation.